Developing Students Communicative Competence using Authentic Materials with Information Technologies - Yusupalieva, Shakhnoza (International Journal of Industrial Engineering, Technology & Operations Management, 2024)
In the globalized landscape of higher education, developing communicative competence in foreign language learners is essential for academic, social, and professional success. This article explores innovative, student-centered strategies beyond traditional grammar-based instruction to enhance linguistic proficiency, cultural understanding, and pragmatic awareness. This study highlights their impact on fostering real-world communication skills by emphasizing interactive methods such as role-playing, task-based learning, debates, and integrating authentic materials. Furthermore, the findings demonstrate that students engaging in these approaches show marked improvements in fluency, adaptability, and cultural sensitivity. Role-playing scenarios and debates enhance spoken communication, critical thinking, and argumentation skills, while task-based activities encourage collaboration and purposeful language use. Exposure to authentic resources bridges the gap between classroom learning and practical application, deepening students' comprehension of idiomatic expressions, cultural norms, and socio-linguistic nuances. Despite challenges like resource limitations and technological barriers, the study underscores the transformative potential of these methods. By addressing implementation hurdles through digital innovation and tailored pedagogy, educators can create a robust framework that prepares students for the demands of global communication. This article advocates for continued research and adaptation to refine these strategies, ensuring their effectiveness across diverse educational contexts.